The Political Empowerment of the Cocaleros of Bolivia and Peru - Ochoa, Ursula Durand; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book offers a comparative analysis of the distinct experiences of the Peruvian and Bolivian cocaleros as political actors. In doing so, it illustrates how coca, an internationally criminalzsed good, affected the path and outcome of cocalero political empowerment in each case.
Keywords: Science; Science; Science, general